PEMBUATAN SABUN KERTAS EKSTRAK BUNGA TELANG DENGAN VARIASI SUHU DAN PENGADUKAN - Novitasari, Aprilia Donna; Puspitasari, Dewi Fitriani; Ariani, Lilies Wahyu (Jurnal Farmasi & Sains Indonesia, 2025)
Soap is a health supply that is much needed to maintain cleanliness. Telang flowers have the potential to inhibit Staphylococcus aureus bacteria, so that their potential can be utilised in making soap made from nature. One form of soap that is currently trending is paper soap. Formulating bayang flower extract in paper soap making, it is necessary to pay attention to pH and temperature factors, because the colour stability of bayang flower anthocyanins is easily affected by temperature and pH. In paper soap making, temperature and stirring factors will also have an influence on the character of the resulting paper soap. In this study, a study was conducted to make bayang flower paper soap by looking at the effect of temperature during manufacture and stirring on the characteristics of soap including pH, moisture content, and colour of paper soap. The method of making paper soap is conditioned on variations in manufacturing temperature, namely 77 ° C, 85 ° C and 92 ° C and variations in stirring speed at 280, 350 and 420 rpm. The telang flower extract was made using the maceration method in a ratio of 1:6, using a combination of 70% ethanol and 0.42% NaOH solvents (6:4), the extract was used with a concentration of 10%. The results show that paper soap made with increasing temperature and stirring has a decreasing pH value and moisture content and has a darker green colour variation. Keywords: bay flower, paper soap, temperature